The Effect Of Communication On Employee Performance With Organizational Culture As A Moderation Variable At The Sidikalang Sub-District Office - Abdimar Jahotlen Tamba; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2025)
Communication and work discipline are two crucial factors that can affect employee performance. This study aims to find out and analyze the role of organizational culture and communication on employee performance with organizational culture as a moderation variable at the Sidikalang District Office. The approach used is quantitative causal associative, with a sample consisting of all employees in the sub-district office, namely 49 people. The results of data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) show that: 1) Organizational culture has a positive and significant effect on employee performance with a T-statistic value of 5.327 > 1.96 and a P-value of 0.000 < 0.05; 2) Communication did not have a significant effect on employee performance with a T-statistic value of 0.415 < 1.96 and a P-value of 0.680 > 0.05; and 3) Organizational culture was not able to significantly strengthen the influence of communication on employee performance with a T-statistic value of 0.738 < 1.96 and a P-value of 0.464 > 0.05. These findings indicate that a strong organizational culture plays an important role in improving employee performance, while communication, while important, does not have a significant impact on performance in the context of this study. This shows that in addition to a supportive organizational culture, other factors also need to be considered to improve employee performance optimally.